RS4 Type Resistant Starch Improves Type 2 Diabetes Mellitus in Mice by Interacting With Lactobacillus johnsonii - Tao Xu; Yongheng Zhong; Shengyang Ji; Hang Xiao; Jun Li; Kaimian Li; Peiwu Li; Baiyi Lu (Food Frontiers)
ABSTRACT RS4‐type resistant starches have been applied in food industry as thickeners or studied as functional foods for a long time. However, the influence and mechanism of RS4 on Type 2 diabetes mellitus (T2DM) have not been elucidated. In this study, sinapic acid starch ester (SASE) was chosen as a representative of functional RS4, and its anti‐diabetic activity and underlying mechanism were investigated. Results showed that SASE administration lowered blood glucose and ameliorated insulin resistance of streptozotocin‐induced diabetic mice via increasing serum butyrate level. Fecal microbiota transplantation confirmed the T2DM‐improving activity of SASE modulated gut microbiota. 16S rRNA gene sequencing indicated that SASE selectively promoted the proliferation of butyrate‐producing bacterium. In vitro co‐culture of promoted gut bacterium with SASE revealed that Lactobacillus johnsonii was one of the key bacteria in the degradation of SASE. In conclusion, RS4 could selectively promote gut bacteria and increase short‐chain fatty acid production to alleviate T2DM.